Phonecardoperated payphones in buses in Brazil - Tavares, Wagner de Souza (DAT Journal, 2021)
Payphones were installed in public buses in Brazil. These payphones worked with same phonecards used in tradicional payphones or with specific phonecards produced by telecommunication companies in collaboration with bus transport companies. The objectives of this study were to identify the buses installed with payphones in Brazil, chronology, payphone system, and phonecard type (whether tradicional or specific). The specific phonecards were described. A mobile phone-type payphone working with tradicional phonecards, developed by Telecomunicações da Paraíba S.A. (TELPA; João Pessoa, Paraíba State, Brazil) and installed in 1994 on Rogetur Transporte e Turismo Ltda. transport company buses, is the first consolidate case of a payphone used in a bus in Brazil. Specific phonecards developed by Globalstar, Inc. (Covington, Louisiana, United States of America) in 2000 were used in payphones installed on Viação Itapemirim S.A. and Empresa de Ônibus Nossa Senhora da Penha S.A. transport company buses.